1983
DOI: 10.33584/jnzg.1983.44.1617
|View full text |Cite
|
Sign up to set email alerts
|

Legume Oversowing on Hill Country in Marlborough

Abstract: Legumes oversown onto hill country in Marlborough were compared in six trials. At low altitude sites with northerly aspects, legume establishment was negligible unless resident vegetation was treated with herbicide prior to oversowing. On a southerly aspect, legumes established without herbicide although yields were higher if it was applied. 'Grasslands Pawera' red clover outyielded other legumes at 350m. producing 4.6 and 10.1 t DM/ha on a sunny and shady face respectively. Pawera also produced more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This may limit the use of lucerne in uncultivable hill country unless methods can be found that reduce moisture stress on seedlings as they emerge and develop. Red clover (Trifolium pratense) is best adapted to moist, cool locations while Caucasian clover (Trifolium ambiguum) is more drought-tolerant but often has low establishment (Rhodes & Clare 1983;Allan & Keoghan 1994;Moorhead et al 1994). Subterranean clover (Trifolium subterraneum) is well adapted to summer-dry hill country where competition (shading) is removed before sowing and the species (Smetham 2003a).…”
Section: Speciesmentioning
confidence: 99%
“…This may limit the use of lucerne in uncultivable hill country unless methods can be found that reduce moisture stress on seedlings as they emerge and develop. Red clover (Trifolium pratense) is best adapted to moist, cool locations while Caucasian clover (Trifolium ambiguum) is more drought-tolerant but often has low establishment (Rhodes & Clare 1983;Allan & Keoghan 1994;Moorhead et al 1994). Subterranean clover (Trifolium subterraneum) is well adapted to summer-dry hill country where competition (shading) is removed before sowing and the species (Smetham 2003a).…”
Section: Speciesmentioning
confidence: 99%
“…Competition from Hieracium will be more intense where soil moisture is limiting (i.e., low rainfall sunny faces), such as the 860 m Queensberry site where Patrick & Lowther (1995) reported that most plants disappeared over summer owing to drought stress. In semi-arid environments, herbicide application may be necessary to control existing vegetation and reduce competition for moisture over the first summer (Rhodes & Clare 1983).…”
Section: Strategies To Maximise Caucasian Clover Establishmentmentioning
confidence: 99%